Joint placement and sleep scheduling of grid-connected solar powered road side units in vehicular networks - D C, Vageesh; Patra, M.; Murthy, C. Siva Ram (Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks (WiOpt), 2014 12th International Symposium on, 2014)
With the emerging demand for vehicular safety and comfort, research in vehicular ad hoc networks (VANETs) has received more importance lately. Road side units (RSUs) being a key element for communication in VANETs, optimal placement of RSUs has become a challenge to ensure ubiquitous connectivity and lower deployment cost. With the emphasis on minimizing carbon footprint, energy aware strategies in placement are necessary. A direction orthogonal to it is sleep scheduling of RSUs to minimize their energy consumption. Taking these into account, we aim to perform optimal placement of RSUs with sleep scheduling where RSUs are powered by conventional grid and solar power. This is done by jointly optimizing the total number of RSUs deployed, the operational expenditure and the conventional grid energy consumed. We use Rainbow Ranking algorithm to place and schedule RSUs for a given scenario. Our results show that this kind of joint optimization leads to an overall energy aware RSU placement with lower overall cost.